A mediação documentária: aspectos epistemológicos, conceituais e procedimentais - Matheus Aguiar de Carvalho (2024)
Documentary mediation is a set of actions on objects to transform them into documents. These actions imply the development of products such as documentary systems, in addition to the provision of services and activities to enhance access and use of the former. The objective of documentary mediation is to satisfy the information needs of audiences in specific contexts. Documentary mediation has traditionally been studied in the disciplines Bibliography, Librarianship, Archival science and Museology, the first two focused on the bibliographical approach to documentary activity, and the next two focused on archival and museological approaches, respectively. The articulation between these disciplines produces the field of documentary studies, also known as Documentation. With the dissemination of Information Science in the United States from the 1960s onwards, the study of documentary mediation was accommodated as one of its themes, which resulted in the partial erasure of its foundations. As a result of this scenario, field research was confronted with the simplification of the notion of documentary mediation, due to the reduction of the scientific community's interest in the topic, simultaneously with the amplification of studies on mediation from the perspective of other disciplines, mainly in the field of social and human sciences. Therefore, the objective of this thesis is to analyze the scientific field of documentary studies to systematize the bases of documentary mediation actions from epistemological, conceptual and procedural aspects. The thesis is basic research, markedly theoretical and exploratory. The method adopted to develop the thesis was bibliographic review. In structural terms, section 2 refers to the epistemological aspects of documentary mediation, regarding its elaboration as an object of study in a scientific field constituted through the relationship between documentary disciplines. Section 3 focuses on the conceptual study of documentary mediation, considering the origin of the term in French production and its development in the Brazilian context. In section 4, the discussion was based on the procedural aspects of documentary mediation, regarding its technical-systemic functioning and the intentions inherent to it. In section 5, we systematize the fundamental categories of documentary studies, exploring documentary mediation as its scientific object and as a social practice. The study allows us to identify the instability that marks the course of the field and highlight the wealth of knowledge developed over time, which, if recovered, would make it possible to highlight the social function of documentary studies in contemporary times, especially in the brazilian context.